The healthy organization a revolutionary approach to people and management - Dive, Brian; Gale Group (London Kogan Page, 2004)
Reveals that the unhealthy features of both large and small organizations all stem from the same source, namely the lack of true decision-making accountability (DMA), and introduces a new approach to leadership development.
The healthy organization -- The empirical evidence -- The decision-making accountability solution set -- How to develop a healthy organization -- How to stimulate genuine empowerment and innovation -- Broadbanding : fool's gold -- The salmon fallacy -- Tracking the salmon -- Mobilizing change.
Electronic reproduction.
Keywords: Personnel management; Electronic books